Psychological wellbeing as a buffer against burnout and anxiety in academic achievement situations among physical education students - Li, Jianye; Li, Yuebo; Li, Keqiang; Lipowski, Mariusz; Shang, Zhan; Wilczyńska, Dominika (Frontiers in Psychology, 2025)
IntroductionThis study examined the complex relationship between burnout, wellbeing, and academic achievement anxiety in physical education students. The focus was on how wellbeing moderates burnout and academic achievement anxiety.MethodsThis study adopted a cross-sectional quantitative survey (n = 523) and used the Maslach burnout inventory–student survey (MBI-SS), Psychological wellbeing scale (PWBS), and Academic achievement anxiety test (AAT) to verify the mediation model of wellbeing among physical education students to identify the impact of wellbeing on burnout.ResultsUsing a range of psychological scales, we found significant positive correlations between self-acceptance and positive psychological dimensions such as Purpose in Life and Environmental Mastery. Facilitating anxiety was found to enhance self-acceptance and professional efficacy, while debilitating anxiety strongly correlated with burnout symptoms, including cynicism and exhaustion. Personal growth and autonomy were positively linked to psychological resilience and wellbeing. The study also highlighted the mediating role of psychological wellbeing in reducing the impact of burnout on academic anxiety.DiscussionThese findings suggest that moderate anxiety can be motivating, but high levels of debilitating anxiety pose a significant risk for burnout. Interventions aimed at fostering emotional resilience, self-acceptance, and personal growth may help mitigate the effects of anxiety and burnout. The study’s limitations include its focus on a specific student population and cross-sectional design, which restricts generalizability and causal inferences. Future research should explore these relationships over time and in broader student populations, incorporating contextual factors and testing intervention effectiveness.